Effective gene-silencing of siRNAs that contain functionalized spacer linkages within the central region. Issue 6 (13th January 2017) - Desaulniers, Jean-Paul; Hagen, Gordon; Anderson, Jocelyn; McKim, Chris; Roberts, Blake
Abstract : Short-interfering RNAs containing a variety of functional groups at the central region of the sense strand were synthesized and evaluated. Abstract : Short-interfering RNAs containing a variety of functional groups at the central region of the sense strand were synthesized and evaluated. The gene-silencing data suggest that these siRNAs are biocompatible and are very effective in cell-based assays.